The benefit of co-targeting PARP-1 and c-Met on the efficacy of radiotherapy in wild type BRAF melanoma - Sabbah, Malak; Najem, Ahmad; Vanderkerkhove, Christophe; Kert, Fabien; Jourani, Younes; Journe, Fabrice; Awada, Ahmad; Van Gestel, Dirk; Ghanem, Ghanem E.; Krayem, Mohammad (Frontiers in Medicine, 2023)
Melanoma is known to be a radioresistant cancer. Melanoma radioresistance can be due to several factors such as pigmentation, antioxidant defenses and high DNA repair efficacy. However, irradiation induces intracellular translocation of RTKs, including cMet, which regulates response to DNA damage activating proteins and promotes DNA repair. Accordingly, we hypothesized that co-targeting DNA repair (PARP-1) and relevant activated RTKs, c-Met in particular, may radiosensitize WTBRAF melanomas where RTKs are often upregulated. Firstly, we found that PARP-1 is highly expressed in melanoma cell lines. PARP-1 inhibition by Olaparib or its KO mediates melanoma cell sensitivity to radiotherapy (RT). Similarly, specific inhibition of c-Met by Crizotinib or its KO radiosensitizes the melanoma cell lines. Mechanistically, we show that RT causes c-Met nuclear translocation to interact with PARP-1 promoting its activity. This can be reversed by c-Met inhibition. Accordingly, RT associated with the inhibition of both c-Met and PARP-1 resulted in a synergistic effect not only on tumor growth inhibition but also on tumor regrowth control in all animals following the stop of the treatment. We thus show that combining PARP and c-Met inhibition with RT appears a promising therapeutic approach in WTBRAF melanoma.